ELABORATION OF THE POLITICAL HISTORY OF ISLAMIC EDUCATION IN INDONESIA - Mahmuda, Amilia; Mistiningsih, Cindy; Anwar, Khoirul; Kholidah, Kholidah; Mahfud, Choirul (EDUKASI: Jurnal Pendidikan Islam, 2019)
Politics has greatly influenced the Islamic education development. In general, the development of Islamic education in Indonesia was divided into four periods that is the 'before independence' period, the ' Old Order ' period, the ' New Order ' period, and the reform period. Indonesian education instilled the practice of dualism in the 'before independence' period. Islamic education in the period is closely watched and does not develop. The second period is 'Old Order', this period took place after Indonesia's independence, in that time, the government has begun to organize all state systems as well as the education system. Many policies related to Islamic education Also are made in the period. The third period is 'New Order', Islamic education is growing significantly in this period, pesantren which has previously only studied religion began to incorporate the general science in its education system. Students in this period also have to take part in religious education ranging from basic education to the highest education. The fourth period is reform, in this period, the development of Islamic religious education was very much considered and equaled its position with general education.